2021
DOI: 10.21511/bbs.16(2).2021.05
|View full text |Cite
|
Sign up to set email alerts
|

The use of biometric technologies for bank transaction security management against the background of the international experience: Evidence from Ukraine

Abstract: In view of the expanding range of banking services in Ukraine, the issue of introducing innovative means of protecting consumers against illegal actions in the field of banking becomes relevant. This paper aims to determine the effectiveness of biometric technologies for customer identification during banking transactions, the legality of their use, and to identify areas for the development of state policy focused on the legal use of biometric data in order to protect the rights and legitimate interests of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The use of mobile banking applications with AI elements, for example, FacePay in Privat24 allows payment using the user's face with additional confirmation in the bank application. A certain level of security could also be provided by biometric identification (Kurylo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The use of mobile banking applications with AI elements, for example, FacePay in Privat24 allows payment using the user's face with additional confirmation in the bank application. A certain level of security could also be provided by biometric identification (Kurylo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Marketing and Management of Innovations, 2021, Issue 2 263 http://mmi.fem.sumdu.edu.ua/en researched for this case study. It was done in different fields, such as staff management in banking activity (Kurylo et al, 2021), in the sphere of staff recruitment for vacant positions with the application of social networks (Klietsova and Mykhailova, 2021), when the process of digitalization is extending very quickly and the question how to involve the human beings for the long-term care insurance was raised. It was done the preliminary investigation (Klietsova and Zhang, 2020;Szostek, 2021;Kuznichenko et al, 2021) as to the optimization of the labor rights' violation during the pandemic «2019-nCoV», and it was also concluded that the willingness and ability of long-term care insurance could be one of the tools that help to overcome the unpredictable circumstance; as well as was researched the impact of demographic characteristics on counterproductive work behaviors.…”
mentioning
confidence: 99%